A Modified Efficient Traffic Scheduling Algorithm for Routing in Optical WDM Mesh Networks - Kavitha, T.; Rajamani, V. (Journal of optical communications, 2013)
This paper is proposing an efficient traffic scheduling for routing in optical networks supported by Wavelength Division Multiplexing (WDM). Normally the traffic is routed through the primary path or back-up path towards the destination. In order to meet the transmission of higher data rates, the path of the WDM should be capable of carrying the traffic without any failure. Whenever the transmission through primary or backup path fails due to excessive overhead or network failure or congestion or excessive load, existing router mechanisms are not scheduling the traffic in an effective manner. This paper deals with an efficient traffic scheduling algorithm which effectively routes the traffic using multipath technique that satisfies the optical constraints. The whole procedure of routing algorithm is separated into two phases: the connection node establishment phase and multipath transmission from the connection node to destination phase. The connection node is selected on the basis of load and current traffic carrying capacity of that node. Then the traffic is routed to the destination using multiple paths. The proposed method tries to minimize the blocking probability of 70% compared to the existing Resource Efficiency Factor (REF) algorithm and also increase the throughput of 30% and better channel utilization of 23% based on data rate and 20% based on traffic time interval. Hence, the proposed algorithm is effectively routes the traffic within the network.